Dopamine-Mediated Oxidation of Methionine 127 in α-Synuclein Causes Cytotoxicity and Oligomerization of α-Synuclein - Nakaso, Kazuhiro (Public Library of Science, 2013)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the selective loss of dopaminergic neurons and the presence of Lewy bodies. Many recent studies focused on the interaction between α-synuclein (α-syn) and dopamine in the pathogenesis of PD, and fluorescent anisotropy suggested that the C-terminal region of α-syn may be a target for modification by dopamine. However, it is not well understood why PD-related pathogenesis occurs selectively in dopaminergic neurons. We investigated the interaction between dopamine and α-syn with regard to cytotoxicity. A soluble oligomer was formed by co-incubating α-syn and dopamine in vitro. To clarify the effect of dopamine on α-syn in cells, we generated PC12 cells expressing human α-syn, as well as the α-syn mutants, M116A, Y125D, M127A, S129A, and M116A/M127A, in a tetracycline-inducible manner (PC12-TetOFF-α-syn). Overexpression of wildtype α-syn in catecholaminergic PC12 cells decreased cell viability in long-term cultures, while a competitive inhibitor of tyrosine hydroxylase blocked this vulnerability, suggesting that α-syn-related cytotoxicity is associated with dopamine metabolism. The vulnerabilities of all mutant cell lines were lower than that of wildtype α-syn-expressing cells. Moreover, α-syn containing dopamine-mediated oxidized methionine (Met(O)) was detected in PC12-TetOFF-α-syn. Met(O) was lower in methionine mutant cells, especially in the M127A or M116A/M127A mutants, but also in the Y125D and S129A mutants. Co-incubation of dopamine and the (125)YEMPS(129) peptide enhanced the production of H(2)O(2), which may oxidize methionine residues and convert them to Met(O). Y125- or S129-lacking peptides did not enhance the dopamine-related production of H(2)O(2). Our results suggest that M127 is the major target for oxidative modification by dopamine, and that Y125 and S129 may act as enhancers of this modification. These results may describe a mechanism of dopaminergic neuron-specific toxicity of α-syn in the pathogenesis of PD.